The Phenomena of Copyright Infringement in Digital Marketing Towards Creative Ideas - Ari Susanti (Kanal: Jurnal Ilmu Komunikasi, 2023)
The purpose of this study is to dissect the phenomenon of Copyright infringement that often occurs in digital marketing related to creative ideas. This study used qualitative research methods by conducting in-depth interviews with owners of Micro, Small and Medium Enterprises in the culinary sector to explore as much data as possible from informants. The result of this study is that Micro, Small and Medium Enterprises are reluctant to register their chip rights because of complicated procedures, require a long time, the costs incurred are relatively expensive and a pessimistic sense of the sustainability of their business in the future. Therefore, it is necessary to socialize Micro, Small and Medium Enterprises to consciously protect themselves against their creative ideas through Intellectual Property Rights (IPR). Moreover, the process of creative ideas arises because of efforts to develop something and even find new findings as an effort to refine previous ideas through a long process and a long time for perfecting the idea and not a small cost. With the protection of ideas, the spirit to create will grow and develop without limits. In addition, business actors and the public in general understand about the Consumer Protection Law and the Electronic Information and Transaction Law where sanctions for theft of creative ideas have been strictly regulated in it.